Immune-Mediated Association Between Celiac Disease and Sensorineural Hearing Loss: A Systematic Narrative Review - De Luca, Pietro; Scarpa, Alfonso; Ralli, Massimo; Tassone, Domenico; Cassandro, Claudia; Simone, Matteo; de Campora, Luca; Camaioni, Angelo (Turkish Journal of Gastroenterology, 2022)
The auto-immune correlation between sensorineural hearing loss and celiac disease has previously been hypothesized. This review describes available evidence and offers insights for future perspectives. We searched the PubMed database. Studies in the review included children and adults with celiac disease evaluated for hearing loss. Individual case reports and review articles were excluded. The various searches turned in 32 results, of which 10 met the inclusion criteria. Auto-immune hearing loss has been proposed as extra- intestinal symptoms of celiac disease, despite the pathogenetic mechanisms being not entirely clear. Several studies postulated that subclinical hearing loss may be present in children with celiac disease. Despite existing literature not clarifying the link between celiac disease and sensorineural hearing loss, some authors proposed hearing screening in younger patients with celiac disease, to prevent the behavioral, cognitive, and sensorimotor impairment of hearing loss. Further rigorous studies are strongly recommended to better explore the relationship between hearing loss and celiac disease.